Effectiveness of Trainings Funded by Development Partners in Egyptian Government Organizations - Walid, Mariam (AUC Knowledge Fountain, 2023)
The thesis explores the effectiveness of trainings provided through development partner funding to the Egyptian government. Egypt is receiving a moderate amount of funding from development partner, as an emerging economy . The development assistance reached 1.56 billion US dollars where a good amount of it is directed towards capacity development and training. In light of the current public administration reform, specifically the efforts in public administration reform, Egypt needs skillful employees to enhance the governmental performance and help it achieve its strategic 2030 vision. Accordingly, it is very important to understand the effectiveness of the trainings provided by development partners to support the national development goals, and to try to figure out the effect of those trainings on individuals and organizations. This study portrays an angle of capacity development that is not explored enough in Egypt, yet is crucial in the current times. The conceptual framework used was developed by the researcher through an adaptation of several concepts and frameworks, including results-based management, logical framework and systems thinking. The purpose was to explore training from different angles, and from the point of view of different stakeholders, focusing not only on internal individual and organizational factors, but also on external factors. The study uses an exploratory qualitative approach, with semi structured interviews as the main data collection. 15 interviews were done with development partner organizations and government organizations in addition to other stakeholders like implementing agencies and training providers. The analysis concentrated on both government and development partner side and tried to understand further the effect of Covid-19 on these trainings. The findings of the study showed the pitfalls affecting the training effectiveness. Most importantly the governance of training from the government’s side in addition to the practices done by development partner organizations that needs to be adjusted to increase the effectiveness of trainings.